Assessment of Selected Models for FRP-Retrofitted URM Walls under In-Plane Loads - Marijana Hadzima-Nyarko; Stanko Čolak; Borko Đ. Bulajić; Naida Ademović (Buildings, 2021)
One way to improve a structure’s total load-bearing capacity during an earthquake is to apply fiber-reinforced polymers (FRP) to unreinforced walls. The study discusses the use of FRP to strengthen unreinforced masonry (URM) structures. Although, many studies were conducted on the FRP strengthening of URM buildings, most of them were experiments to investigate the success of retrofitting approaches, rather than developing a successful design model. A database of 120 FRP-reinforced wall samples was created based on the current literature. Various approaches for calculating the bearing capacity of FRP-reinforced masonry are presented and detailed. The findings of the experiments, which were compiled into a database, were compared to those derived using formulas from the literature and/or building codes, and the model’s limitations are discussed.